A new goatfish of the genus Upeneus (Mullidae) from Angoche, northern Mozambique - Uiblein, Franz; Lisher, Mark (Zootaxa, 2013)
A new goatfish, Upeneus saiab n. sp. (Mullidae), is described from six specimens collected off Angoche, northern Mozambique, during a research cruise of the RV Dr. F. Nansen in August 2009. Upeneus saiab n. sp. differs from all congeneric species in the following combination of characteristics: seven dorsal-fin spines, 29 total gill rakers, body depth at anal-fin origin 17–19% SL, and pectoral-fin length 20–21% SL. Detailed comparisons with the eight other species of the japonicus group are made and a key for Western Indian Ocean species is provided. A new record of Upeneus pori for KwaZulu-Natal, South Africa, is reported based on in situ photographs. The need for further exploration of the rather long and ecologically diverse Mozambican coast and adjacent areas of southeastern Africa for the occurrence of yet undescribed or unreported goatfish species is emphasized.